Dampak Pemberian Teh Daun Kelor (Moringa oleifera) terhadap Kadar Glukosa Darah pada Penderita Diabetes Melitus Tipe 2 di Wilayah Puskesmas Kecamatan Cakung, Jakarta Timur - Kiti Rofianti; Septiani Septiani (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2022)
The content of epigallocatechin-3-gallate (EGCG) in moringa leaves which has antioxidant properties and acts as an antidiabetic can help lower blood glucose levels. This type of research is experimental, with a pretest-posttest control group design and a quantitative approach. Respondents in this study were 30 people, with 15 in the control group and 15 in the intervention group. Respondents must meet the inclusion criteria, namely suffering from type 2 diabetes mellitus according to data from the Cakung Sub-district health center, East Jakarta, aged 45 to 74 years having mild to moderate physical activity, and not suffering from complications and taking drugs from health workers. Respondents measured their initial blood glucose levels (pretest), then were given treatment by giving moringa leaf tea as much as 200 ml, after that the final blood glucose levels were measured (posttest). The decrease in blood glucose levels in the control group was 21.6 mg dL-1 and the decrease in blood glucose levels in the intervention group was 29.7 mg dL-1. Giving moringa leaf tea brewed in 200 ml of water can significantly impact blood glucose levels in patients with type 2 diabetes mellitus, which marks a decrease in blood glucose levels after treatment, with p-value < 0.05. There is a significant effect on reducing blood glucose levels in patients with type 2 diabetes mellitus with p-value < 0.05 after giving 200 ml of moringa leaf tea (p-value 0.01) so that it can be used as an alternative to lower blood glucose levels for diabetics.